IJCM_403A: Breakfast Skipping: Proportion and Awareness of its Effects Among Medical Students - Vaibhav Swayam; Thomas Shilpa; Palki; Chaudhary Nikita; Kalyani P.; Rekha T; Unnikrishnan Bhaskaran; Mithra Prasanna; Kumar Nithin; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Breakfast is considered the most important meal of the day, providing essential nutrients and energy needed for daily activities. Skipping breakfast has been associated with various health complications, including impaired cognitive function and increased risk of chronic diseases. Understanding the prevalence and reasons behind breakfast skipping among medical students is crucial for promoting healthy habits and overall well-being. Objectives: This study aimed to determine the proportion of medical students skipping breakfast, assess awareness about the importance of breakfast consumption, and explore associated factors such as gender and academic semester. Methodology: A cross-sectional study was conducted among medical undergraduates at Kasturba Medical College, Mangalore. A semi-structured questionnaire was administered to 285 students from the 2nd, 3rd, and 4th year MBBS classes. Convenience sampling was used, and data were analysed using descriptive statistics and chi-square tests. Results: Of the 285 students surveyed, 53% reported skipping breakfast. Reasons for skipping included waking up late (77.48%), dissatisfaction with available food options (44.37%), and lack of appetite (21.85%). While most students were aware of the negative effects of breakfast skipping on cognitive function and mood, fewer recognized its association with cardiovascular problems and menstrual irregularities. Significant associations were found between breakfast skipping and academic semester, with 6th-semester students exhibiting the highest prevalence. However, no significant gender differences were observed. Conclusion: The study highlights a concerning prevalence of breakfast skipping among medical students, emphasizing the need for targeted interventions to promote healthy breakfast habits.